(untitled) (Texas Journal of Medical Science, 2022)
The importance of the research was demonstrated through the development of an analytical study of the reality of digital culture as a source of classroom management in the light of the requirements of quality management among handball teachers in the faculties of physical education and sports sciences as one of the standards of quality management and thus identify the strengths and weaknesses of this important axis and to contribute to the development of the performance of handball teachers specialization The researcher has used the survey approach The research sample was selected in a random way divided into two samples of the first sample of (64) for the building sample and on A second sample of (74) handball teachers specializing in universities for the sample of application person and a questionnaire form or scale (digital culture) was designed, namely (cognitive potential, material potential, the use of digital technology and the obstacles of digital culture) and after distributing The questionnaire and collecting the results the researcher reached the following conclusions: that handball teachers in Iraqi potential universities have a good level of knowledge in the measure of digital culture and that they have an average level of digital culture